Fair trade marketing - an ethical edge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Honey Care Africa is a company based in Kenya which in the last two years has won numerous awards for its development work with small-scale, rural beekeepers. The company?s marketing strategy has focussed on having a good quality, attractively labelled product, but it is also aware that being a ?Fair Trade? producer also helps to attract customers.